Asimmetrie e sviluppo in Europa - Carlucci, Francesco (Rivista di studi politici internazionali, 2007)
In the European Union many and also deep differences exist between member States and it is likely that they constitute one of the main causes of the unsatisfactory convergence in the growth of European economies. Faced with this asymmetry in growth, a widespread thought advocates a greater smoothing of initial differences, asserting that, once these are reduced, income dissimilarities in the Countries would be lowered, their economic growths would be similar, and Europe could develop quickly. Thus, member States should have – it believes – a similar production structure, similar social systems, similar economic, energy, infrastructural, and so on, policies. Another widespread thought realizes the operative difficulties in eliminating such initial differences, particularly in the short run, and affirms that every member State could improve its own growth by means of a more effective use of national policies and a better exploitation of internal specificities. Asymmetries in economic growth between Countries – it believes – would vanish and the European Union could develop at a quicker pace. However, these two lines of thought are essentially theoretical. In front of real problems they are firstly evoked as compasses for their solution, but soon they are replaced with less noble operative procedures, so that most decisions are taken either under the pressure of powerful lobbies or in function of pure national targets, often worsened by the establishment of bilateral relationships with non-European States. These argumentations are illustrated by four relevant cases, for each of which firstly the negative aspects of the current situation are shown, afterwards the interventions are pointed out that the two lines of thought would put forward in order to eliminate them, and finally the approach actually followed by Union’s Countries is illustrated, enlightening lobbies’ work, the privileges accorded to the national targets compared to the supranational ones, as well as the quest for benefits operated by bilateral policies. Afterwards, we propose a different decision-making approach, which not only maximizes the European collective well-being defined by a specific criterion, but also is based on the consensus of all parties. First of all, we affirm that the development of a Country cannot be evaluated in terms of economic wealth only, but has to take other main aspects of well-being into consideration: employment, honesty and safety mean levels, political and civil rights, health and educational structures, environment, cultural and natural heritages, and obviously, but not in a hegemonic way, income and its distribution. Thus, the development of a Country is measured not by a specific economic value, say income, but through an index that takes all fundamental aspects of well-being into consideration, aggregating them by a way that does not use the monetary measure. Once such a well-being index is constructed by mutual consensus (and in this construction the political side of the mechanism resides), its value for each intervention is computed, and the intervention associated with the highest value of the index (that is of well-being) is chosen. RÉSUMÉ - Dans l’Union Européenne il y a beaucoup de différences parmi les États membres, qui constituent une des causes principales de la convergence insatisfaisante qui existe dans la croissance des économies européennes. En présence de cette asymétrie dans la croissance, une pensée répandue intervient en faveur d’un plus grand nivellement des différences initiales en affirmant que, une fois qu’elles sont réduites, les différences de revenu dans les Pays pourraient aussi être réduites, leur croissance économique serait presque la même, et la société européenne pourrait se développer plus rapidement. Ainsi les États membres de l’Union devraient avoir des structures productives semblables (la même haute efficacité dans les processus de production et la même maturité des produits), des systèmes sociaux semblables, des politiques économiques, énergétiques, infrastructurales semblables etc. Une autre pensée très répandue se rend compte des difficultés opératives de éliminer ces différences initiales, spécialment dans la période brève, et affirme que chaque Pays membre pourrait améliorer sa propre croissance en utilisant dans la manière la plus incisive les politiques nationales et en exaltant les spécificités intérieures. Ainsi l’asymétrie dans la croissance économique entre les Pays pourrait disparaître et l’Union pourrait se développer plus. Les deux pensées sont plutôt théoriques. En présence de problèmes réels elles sont d’abord évoquées comme étoiles polaires pour leur résolution, mais elles sont bien rapidement remplacées par des procédures opératives moins nobles, ainsi que la grande partie des décisions est prise sous la pression de lobbies très puissants ou en fonction d’objectifs purement nationaux, souvent aggravés par l’instauration de relations bilatérales avec Pays extra-communautaires. Ces argumentations sont illustrées par des examples en quatre cas considérables (chaussure, substances polluantes, énergie électrique, Airbus). Pour chacun de ces cas on a d’abord illustré des aspects négatifs de la situation actuelle, on a donc indiqué les interventions que les deux pensées proposeraient dans l’intention de les éliminer. Enfin on illustre l’approche effectivement suivie par les Pays de l’Union, en mettant en évidence l’intervention des lobbies, les privilèges accordés aux objectifs nationaux par rapport à ceux supranationaux, ainsi que la recherche de bénéfices, obtenus par politiques bilatérales. Ensuite nous proposons une approche décisionnelle différente, que non seulement maximise le bien-être collectif européen défini par un critère spécifique, mais que en plus se base sur le consensus de toutes les parties. Nous affirmons surtout que le développement d’un Pays ne peut pas être évalué seulement en ABSTRACTS - RÉSUMÉS 334 RSPI - N° 295, 3/2007 termes de richesse économique mais qu’il faut qu’il prenne en considération d’autres aspects fondamentaux du bien-être: emploi, niveau moyen d’honnêteté et de sécurité, droits civils et politiques, structures sanitaires et de l’éducation, environnement, patrimoines cultural et naturel, et évidemment, mais non de manière hégémonique, aussi le revenu et sa distribution.